A RARE PRESENTATION OF MEDULLARY THYROID CARCINOMA: A CASE REPORT - Augustine, Amie-Anne; Ho, Jin Hui; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumour arising from the parafollicular C cells of the thyroid gland, accounting for approximately 4% of all thyroid malignancies. We present a case of MTC with an unusual and life-threatening initial manifestation — cardiac tamponade — which led to the diagnosis. CASE A 63-year-old Kadazan male with a medical history of myocardial infarction with non-obstructive coronary arteries (MINOCA) in 2017, intracranial haemorrhage in 2018, polycythaemia rubra vera, dyslipidaemia, hypertension, and type 2 diabetes mellitus, presented with a three-day history of exertional dyspnoea and chest tightness. He also reported a gradual neck swelling and unintentional weight loss over the past year. Initial chest radiography revealed a right lower zone lung opacity, and he was empirically treated for pneumonia. However, a neck ultrasound demonstrated a right thyroid nodule categorized as TIRADS 4, raising suspicion for malignancy. A contrast-enhanced CT (CECT) of the thorax revealed a suspicious right thyroid nodule with bilateral cervical, supraclavicular, and mediastinal lymphadenopathy, multiple pulmonary nodules, a segment VIII liver lesion, and a significant global pericardial effusion measuring 2.8 cm. Fine needle aspiration cytology (FNAC) of the right thyroid nodule and left cervical lymph node confirmed medullary thyroid carcinoma, with positive staining for calcitonin and amyloid deposits identified via Congo red staining. Transthoracic echocardiography showed right atrial and right ventricular collapse, consistent with cardiac tamponade. Emergency pericardiocentesis was performed, and cytology of the pericardial fluid confirmed metastatic MTC. Further laboratory evaluation revealed markedly elevated serum calcitonin and carcinoembryonic antigen (CEA), along with raised urinary levels of normetanephrine, metanephrine, and 3-methoxytyramine, suggesting a paraneoplastic neuroendocrine profile. Germline RET mutation analysis could not be performed due to resource limitations. Given the presence of distant metastases and extensive locoregional disease, the patient was scheduled for systemic therapy with Cabozantinib with plans for total thyroidectomy following tumour debulking. CONCLUSION This case highlights a rare and aggressive presentation of medullary thyroid carcinoma (MTC), manifesting as cardiac tamponade — a life-threatening complication seldom associated with thyroid malignancies. The diagnosis was confirmed through cytological evaluation and supported by elevated tumour markers and imaging. This case underscores the importance of considering metastatic MTC in patients with unexplained pericardial effusion and systemic symptoms, especially in the presence of a suspicious thyroid lesion. Prompt recognition and multidisciplinary management are crucial in optimizing outcomes in such advanced and atypical presentations.